Proceedings of GeoShanghai 2018 International Conference: Fundamentals of Soil Behaviours (Springer Singapore, 2018)
This book is the second volume of the proceedings of the 4th GeoShanghai International Conference that was held on May 27 - 30, 2018. The book, entitled "Fundamentals of Soil Behaviours", presents the recent advances and technology in the understanding and modelling of fundamentals of soil's behaviours. The subject of this book covers a wide range of topics related to soil behaviours in geotechnical engineering, geoenvironmental engineering and transportation engineering. The state-of-the-art theories, methodologies and findings in the related topics are included. This book may benefit researchers and scientists from the academic fields of soil and rock mechanics, geotechnical engineering, geoenvironmental engineering, transportation engineering, geology, mining and energy, as well as practical engineers from industry.